(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article’s aim is to explain to all of you how to live correctly and how to get a joyful life expectency. And hopefully i will write this for you that you could find your own ikigai in any branch of your entire world. If you read this article, you will be in better position than you were. If you have not found your ikigai yet, you will start searching from the space around you or if you have already found it, you will keep dealing with it.